H 2 sensor based on Au/TiO 2 nanoparticles synthesized by flame spray pyrolysis - Chomkitichai W. (2014)
TiO 2 is used extensively as a gas sensing material due to its change in electrical conductivity under analyst gas exposure. Gold (Au) is a good catalyst that promotes chemical reactions by reducing the activation energy between sensing film and particular gas. Unloaded TiO 2 and TiO 2 nanoparticles loaded with 0.25-0.75 at% Au were successfully produced in a single step by Flame spray pyrolysis (FSP) technique. The structure and morphology of as-prepared products have been characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM). TiO 2 and Au-loaded TiO 2 nanoparticle films were prepared by spin-coating technique. The gas sensing of H 2 was studied at the operating temperatures ranging from 300-350°C in dry air. It was found that the TiO 2 loaded with Au sensing film showed higher response of H 2, with faster response time (within second) than pure TiO 2 sensing film. The response increased and the response time decreased with increasing of H 2 concentration.